(untitled) (Bangladesh Rice Journal, 2025)
The use of improved high-yielding modern rice varieties can reduce hunger and food insecurity in country like Bangladesh. But lower adoption and higher adoption gap of modern rice varieties is one of the main concerns of rice researchers, extension specialists, and legislators. This study attempts to determine the adoption and adoption gap of 10 selected BRRI-released Boro rice varieties; assess some selected socio-economic characteristics of the rice farmers; and explore the contribution of the selected socio-economic characteristics of the farmers to their adoption gap of selected BRRI-released Boro varieties. Necessary data were collected during 03 September to 31 December 2021 using a well-structured pre-tested interview schedule from 371 randomly selected farmers covering 12 blocks of 4 (four) upazila under Cumilla, Mymensingh, Tangail, and Bogura districts. The study revealed that most (73.05%) of the rice farmers had high adoption and low adoption gap; 23.72% of them had moderate adoption and adoption gap; and rest 3.23% respondent farmers had low adoption and high adoption gap of BRRI released Boro rice varieties. Overall adoption and adoption gap of BRRI-released Boro rice varieties were 77.02% and 22.98% respectively. Based on descending order of Adoption Index, BRRI dhan29 ranked 1st, followed by BRRI dhan28. Adoption Index of these two top ranked varieties (BRRI dhan29 and BRRI dhan28) were 38.84 and 30.43 respectively which were much higher than others. Third to nineth ranked varieties were BRRI dhan58, BRRI dhan89, BRRI dhan88, BRRI dhan50, BRRI dhan74, BRRI dhan81 and BRRI dhan63. Reverse ranked orders were observed based on descending order of Adoption Gap Index (AGI). Stepwise multiple regression analysis indicated that ‘knowledge on BRRI release Boro rice varieties’, ‘extension contacts’, ‘rice farming profitability’, ‘rice farming experience’, and ‘satisfaction on BRRI released Boro rice varieties’ of the farmers had significant negative contribution to their adoption gap, i.e., positive contribution to their adoption of BRRI-released Boro rice varieties. Based on the findings, the study concluded that policy interventions should be taken to improve farmers’ knowledge on BRRI-release Boro rice varieties by increasing extension contact to all the lower and higher experienced farmers to make them profitable and satisfied to increase adoption and decrease adoption gap of BRRI-released Boro rice varieties. These issues also urge policy interventions for rethinking of current dissemination tactics to ensure the widespread adoption of newly released modern Boro rice varieties at the farm level. Bangladesh Rice J. 27(1): 31-48